Finishing touches - Kerr, Jean frey50 (Doubleday & Company, Inc. Garden City, New York, 1973)
Jeff and Katy Cooper have been happily married for years, but connubial bliss is grinding to something of a halt in the groves of Academe: Jeff, at the age of forty-three, thinks he's fallen in love with one of his poetry students. Then son Steve arrives home from college with his roommate Phil (short for Felicia) and a lady-chasing neighbor (long an admirer of Katy's) keeps turning up like a bad penny. Put them all at the same table and a quiet family dinner turns into a real free-for-all as Jeff runs off with Felicia and Katy--"the last of the Latter-Day Saints"--decides to try a fling herself.
Keywords: American Drama -- Plays -- 20th Century